Patients\' Perspectives on Responsiveness in Outpatient Clinics of Hospitals at Zanjan University of Medical Sciences - Ali Mohammadi; Koorosh Kamali (Preventive Care in Nursing and Midwifery Journal, 2015)
Background and Objectives: According to the World Health Organization (WHO), responsiveness is the ability of health systems to meet the legitimate expectations of populations for non-clinical enhancing aspects of health system. Assessment of responsiveness can help to manage resource allocation and improve strategies. The aim of this study was to assess the responsiveness in outpatient clinics of Zanjan. Materials and Methods: This cross-sectional study was carried out in Zanjan hospitals’ outpatient clinics during 2013-2014. A total of 240 patients were selected systematically. The WHO’s responsiveness questionnaire was used to collect data. Data were analyzed using the descriptive and analytical statistics such as mean, frequency, percent, and the Student t -test and one way ANOVA in the SPSS 11.5. Results: The majority of the respondents (over 73%) rated all aspects of the responsiveness as important. Half of the participants (50.6%) rated overall responsiveness as good. The best performance of responsiveness was related to confidentiality (76.3%) and dignity (63.8%) domains. The dignity was rated as the most important domain from outpatients' point of view. There was a statistically significant difference between the male and female patients regarding mean score of dignity. Conclusion: The finding of this study showed that there were gaps between the responsiveness performances and importance of all domains of the responsiveness. Achieving desirable status of responsiveness is essential.